The good egg - Tamaki, Mariko (Tamaki, Mariko. Lumberjanes, 2018)
It's time of for the camp-wide theatrical festival at Miss Quinzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady Types, but April has writer's block, Jo wants to only work with the stage crew, and Ripley keeps sneaking off to take care of Eggie, a giant bird egg she found in the woods. But then egg poachers show up, and Ripley and her friends must use their acting to save the bird.